Trapa bispinosa Roxb. extract lowers advanced glycation end-products and increases live births in older patients with assisted reproductive technology: a randomized controlled trial - Masao Jinno; Ryoji Nagai; Masayoshi Takeuchi; Aiko Watanabe; Koji Teruya; Hikari Sugawa; Naohisa Hatakeyama; Yuichi Jinno (BMC, 2021)
Abstract Background Advanced glycation end-products (AGE), which accumulate with insulin resistance and aging, impair folliculogenesis and may decrease endometrial receptivity. Hishi (Trapa bispinosa Roxb.) extract, a safe herbal medicine, strongly inhibits AGE formation in vitro. We determined whether Hishi lowers AGE and increases live births in older assisted reproductive technology (ART) patients. Methods This prospective randomized open-label controlled trial included 64 patients 38 to 42 years old undergoing ART with or without Hishi extract between June 11, 2015 and July 12, 2019. None had over 2 ART failures, diabetes, uterine anomalies, or exhausted ovarian reserve. After allocation, the Hishi group received Hishi extract (100 mg/day) until late pregnancy or failure. The control group received no extract. Both groups underwent 1 cycle of conventional infertility treatment; 1 long-protocol cycle of ovarian stimulation, oocyte retrieval, in vitro fertilization/intracytoplasmic sperm injection, and fresh embryo transfer (ET); and, if needed, cryopreserved ET until live birth or embryo depletion. Serum AGE were measured before and during ART, as were AGE in follicular fluid (FF). Results Cumulative live birth rate among 32 Hishi patients was 47%, significantly higher than 16% among 31 controls (p<0.01; RR, 4.6; 95% CI, 1.4 - 15.0; 1 control dropped out). Live birth rate per ET, including fresh and cryopreserved, was significantly higher with Hishi (28% in 47 ET vs. 10% in 49 ET; p<0.05; RR, 3.4; 95% CI, 1.1-10.4). Among variables including age, day-3 FSH, anti-Müllerian hormone, and Hishi, logistic regression identified only Hishi as significantly associated with increased cumulative live birth (p<0.05; OR, 5.1; 95% CI, 1.4 - 18.3). Hishi significantly enhanced oocyte developmental potential, improved endometrial receptivity in natural cycles, and decreased AGE in serum and FF. Larger serum AGE decreases with Hishi were associated with more oocytes becoming day-2 embryos. Conclusions Hishi decreased AGE in serum and FF and improved oocyte developmental potential and endometrial receptivity, increasing live births in older patients. Treatment of infertility by AGE reduction represents a new addition to infertility treatment. Therapeutic trials of Hishi for other AGE-associated diseases might be considered. Trial registration UMIN registration in Japan ( UMIN000017758 ) on June 1, 2015. https://www.umin.ac.jp/ctr/index.htm